Aluminium and its soluble inorganic compounds [Air Monitoring Methods, 2014]. Issue 4 (26th October 2016) - Rosenberger, W.; Netz‐Piepenbrink, S.; Hahn, J. U.; Schon, C.; Hebisch, R.; Brock, T. H.; Hartwig, A.; ,
Abstract : This analytical method is a validated measurement procedure for the determination of aluminium and its soluble inorganic compounds in the inhalable and respirable dust fraction in workplace air. Both personal and stationary sampling can be performed for assessment of workplaces. Sampling is carried out by drawing a defined volume of air through a membrane filter located in a sampling head of the sampling device using a suitable pump. The respirable dust fraction is collected with the sampling head FSP 2 or 10 and the inhalable dust fraction with the GSP 3.5 or 10. The dust deposited on the membrane filter is treated with 0.1 M hydrochloric acid at 100 °C and then analysed using atomic absorption spectrometry with the graphite furnace technique (GFAAS). The quantitative determination is based on a calibration function obtained by means of a 10‐point calibration. For the inhalable dust of aluminium the limit of quantification (LOQ) is 0.024 mg/m 3 for a sampling period of two hours (flow rate 3.5 L/min; air sample volume 420 L) and 0.0042 mg/m 3 for the respirable dust for a sampling period of two hours (flow rate 2.0 L/min; air sample volume 240 L). Joint Publication of the Analytical Subcommittee of the Chemistry Board of Experts of the Expert Committee Raw Materials and Chemical Industry of the German Social Accident Insurance and the Working Group "Air Monitoring Methods" of the Permanent Senate Commission of the DFG for the Investigation of Health Hazards of Chemical Compounds in the Work Area.